Development and Validation of a UPLC-MS/MS Detection Method of Baricitinib for Therapeutic Drug Monitoring in COVID-19 Patients - Zhan R; Shen Y; Fu H; Wu H; Chen X; Yu Y; Xu RA (Drug Design, Development and Therapy, 2025)
Ruanjuan Zhan,* Yuxin Shen,* Haoxin Fu, Hualu Wu, Xiaohai Chen, Yige Yu, Ren-Ai Xu Department of Pharmacy, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yige Yu, Email yuyige321@163.com Ren-Ai Xu, Email xra@wmu.edu.cnBackground: Baricitinib is widely used as a selective Janus kinase (JAK) inhibitor for the treatment of immune-mediated inflammatory diseases in clinic. It is now successfully applied in reducing inflammation and suppressing COVID-19-associated immune dysregulation. As knowledge of the appropriate plasma level of baricitinib in COVID-19 patients is deficient, the measurement of the level of baricitinib in plasma during treatment is necessary and important.Purpose: The aim of this study was to establish a bioanalytical method to detect the concentration of baricitinib in COVID-19 patients’ plasma by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS).Methods: The preparation process of the injected sample was to spike 100 μL of plasma and 10 μL of internal standard (IS, upadacitinib) working solution, then add 1:3 of acetonitrile to obtain the supernatant. The intra-day and inter-day precision and accuracy, matrix effect, recovery, and stability of the established methodology were all required.Results: The method was established to determine the plasma levels in 22 COVID-19 patients. After taking 2 mg/day or 4 mg/day of baricitinib, the mean plasma concentrations of the patients were 15.36 ng/mL and 12.64 ng/mL, respectively.Conclusion: This novel UPLC-MS/MS method enables rapid and accurate determination of baricitinib concentrations in human plasma, which is suitable for the therapeutic drug monitoring (TDM) of baricitinib.Keywords: baricitinib, UPLC-MS/MS, drug monitoring, COVID-19